BENTUK DAN FUNGSI PERTUNJUKAN TEATER AMAQ ABIR DI SANGGAR PUSTAKA BUDAYA DESA MARONG KECAMATAN PRAYA TIMUR LOMBOK TENGAH - Zuhri, M. Ihsan; Markarma, Muh Ridwan; Yuliatin, Riyana Rizki (Universitas Hamzanwadi, 2018)
This study aims to describe the form and function of Amaq Abir theater performance at the Marong Village Cultural Literature Studio, Praya Timur District, Lombok Tengah. The research was conducted in Nyampe Hamlet, Marong Village, Praya Timur District. The approach used in this study was qualitative descriptive. The object in this study is the Amaq Abir theatre which includes the form and function of the show. From the results of the study found about: 1) the form of the show, which includes elements in theatrical performances namely: theme, plot, characterization, language, messages, and settings. Supporting elements of the show related to the artistic system, namely: stage management, decoration, sound system, lighting, makeup, and fashion. 2) the theater function of Amaq Abir consists of a) function as entertainment, b) function as social criticism, and 3) function as an economic. Keywords: Form of Performance, Function, Amaq Abir Theater